Literatur Review Trastuzumab Induced Cardiotoxicity (TIC) In Patient With Breast Cancer : Pharmacology Aspect, Mechanism of Cardiotoxicity, Risk Factor and Treatment Strategies - Jaya, Nur (Brawijaya University, 2019)
Background: Breast cancer (BCA) is the most common cancer in women. Since the last 2 decades, early diagnosis and specific molecular targeted neoadjuvant and adjuvant therapy had been reducing breast cancer mortalities. Unfortunately, the improvement of the survival rate is followed by the emergence of cardiotoxicity effect from cancer therapy that had seen in several cases. This showed that trastuzumab treatment significantly affects the functional and structural characteristics of the heart. The mechanism of trastuzumab-related cardiotoxicity is not fully understood. This review will summarize the pharmacology and mechanism of trastuzumab-induced cardiotoxicity, investigate its risk factors, and consider the appropriate management for the patients.Discussion: Trastuzumab is a monoclonal antibody, that acts as human epidermal growth factor tyrosine kinase HER2 (Erb B2) antagonist, frequently given for breast cancer patients. Trastuzumab is not only expressed through the excessive HER2 in positive breast cancer but can also disrupt the cardiomyocytes growth and selectively inhibit the structure and function of the heart causing dilated cardiomyopathy. Some studies recommended angiotensin-converting enzyme inhibitor (ACEI), enalapril, to prevent the late cardiotoxicity and angiotensin receptors blocker (ARB) and also beta-blocker (BB), candesartan and bisoprolol, to significantly reduce LV dysfunction event, as the management of trastuzumab-induced cardiotoxicity.Conclusion: Delaying trastuzumab administration after previous anthracycline treatment can prevent or reduce the risk/synergy effect of cardiotoxicity. The temporal withdrawal and reinitiation after LV systolic function stabilization, both spontaneously or using heart failure therapy, partially succeed in preventing cardiotoxicity. And, monitoring the troponin release was found as the first and the most sensitive test to detect cardiotoxicity early signs, with a proven impact on cardiac prognosis, particularly for trastuzumab (after the previous anthracycline).Keywords: Trastuzumab-Induced Cardiotoxicity; Pharmacology Aspect, Mechanism of Cardiotoxicity, Risk Factor and Treatment Strategies.